Impoliteness Strategies Used by Sylvie Grateau Toward Emily Cooper in Emily in Paris Season One - Tania Silvia Santoso; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2022)
This descriptive-quantitative study is aimed at finding out the types of impoliteness super-strategies used by Sylvie toward her employee, Emily, in Emily in Paris season one, as well as the most and least frequently used types. The main theory used is Culpeper's (1996, 2005) impoliteness strategy. The findings reveal that Sylvie has implemented all five types of impoliteness super-strategies. The most common is negative impoliteness which most likely occurs because Sylvie always opposes Emily on purposes despite knowing how much Emily wants to be professionally acknowledged at Savoir. The least frequently used is withhold politeness, which might happen because although Sylvie is a generally nice person, she uses clearer impolite strategies to Emily on purpose. The writers conclude that Sylvie purposefully uses impoliteness strategies and adds impolite gestures, to bring Emily down and to emphasize her power to get rid of Emily from Savoir. Keywords: impoliteness, impoliteness strategy, status, utterance